Study guides

☆☆

Q: What is the answer of 5c plus 4b - c - 2b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

c-2b

They are terms of an algebraic expression that can be simplified to: 2b+2c

2b + 2c or 2(b + c)

(5c - 2)(c +1)

It is an equation in three unknown variables.

Related questions

c-2b

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b

4b

4b - 2c is an expression, which is equal to 2(2b - c)

a + 2b = c a = c - 2b

2a + 4b + 8c = 2(a + 2b + 4c) You could also continue by factoring the inside of the parentheses a bit: 2a + 4b + 8c = 2(a + 2b + 4c) = 2(a + 2[b + 2c])

c2 + 5c + 6 = (c + 2)*(c + 3)

They are terms of an algebraic expression that can be simplified to: 2b+2c

If: a = 2b+c Then: a-c = 2b And: b = (a-c)/2

a = 2b + c then a - 2b = c ie c = a - 2b

2s-2b= a+b+c-2b simplified that would be a+c-b.

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

People also asked